Hypothalamic Gliosis Associated With High-Fat Diet Feeding Is Reversible in Mice: A Combined Immunohistochemical and Magnetic Resonance Imaging Study - Berkseth, Kathryn E. (Endocrine Society, 2014)
Gliosis, the activation of astrocyte and microglial cell populations, is a hallmark of central nervous system injury and is detectable using either immunohistochemistry or in vivo magnetic resonance imaging (MRI). Obesity in rodents and humans is associated with gliosis of the arcuate nucleus, a key hypothalamic region for the regulation of energy homeostasis and adiposity, but whether this response is permanent or reversible is unknown. Here we combine terminal immunohistochemistry analysis with serial, noninvasive MRI to characterize the progression and reversibility of hypothalamic gliosis in high-fat diet (HFD)-fed mice. The effects of HFD feeding for 16 weeks to increase body weight and adiposity relative to chow were nearly normalized after the return to chow feeding for an additional 4 weeks in the diet-reversal group. Mice maintained on the HFD for the full 20-week study period experienced continued weight gain associated with the expected increases of astrocyte and microglial activation in the arcuate nucleus, but these changes were not observed in the diet-reversal group. The proopiomelanocortin neuron number did not differ between groups. Although MRI demonstrated a positive correlation between body weight, adiposity, and the gliosis-associated T2 signal in the mediobasal hypothalamus, it did not detect the reversal of gliosis among the HFD-fed mice after the return to chow diet. We conclude that hypothalamic gliosis associated with 16-week HFD feeding is largely reversible in rodents, consistent with the reversal of the HFD-induced obesity phenotype, and extend published evidence regarding the utility of MRI as a tool for studying obesity-associated hypothalamic gliosis in vivo.